Zakonodavstva pro admìnìstrativnu proceduru v Ukraїnì : âkim bude vibìr? - Školik, Andrìj (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
The article discusses possible ways for development of Ukrainian legislation on administrative procedure. Unlike majority of the European Union states including Poland, Ukraine does not have general law regulating public administration`s activities. Although three similar drafts of Administrative procedure code have been submitted to Ukrainian parliament during past ten years. At the same time a lot of new laws regulating different areas of public administration’s activities have been adopted. Therefore, there are two possible ways for further development of Ukrainian legislation in analyzed sphere. First, general Administrative procedure code at last will become the key-law and most of previous special legislation will have to be changed according to the new code. Second, new special laws regulating different areas of public administration’s activities will continue to be adopted. The author of the article analyses possible failures and advantages of both ways and finally recommends the first one, which is not the easiest way, taking into consideration contemporary state of Ukrainian legislation in abovementioned sphere
Keywords: Ukraina; ustawodawstwo; procedura administracyjna